El poder de los cuerpos: el desarrollo de la sexualidad y la práctica del aborto en Del rojo de su sombra de Mayra Montero, Wide sargasso sea de Jean Rhys y Moi, Tituba, sorcière… Noire de Salem de Marysé Condé. Un estudio comparado. (El Hilo de la Fabula, 2021)
This work analyzes the manifestations of sexuality and the practice of abortion as elements of subversion linked to the oppressive colonial and patriarchal system that constrains the freedom of the characters in three literary works produced by female Caribbean writers: Del rojo de su sombra (1992) by Mayra Montero, Wide Sargasso Sea (1966) by Jean Rhys and Moi, Tituba sorcière... Noire de Salem (1986) by Marysé Condé. The rewriting processes that originated these literatures reveal voices overlooked through history and literature, from the distancing of the prevailing female models and the (re)valorisation of  body discoverment, sexual experiences and their practices.
Keywords: Sexuality; Body; Abortion; Caribbean literature